Genome-Wide Identification of the MIKC-Type MADS-Box Gene Family in Gossypium hirsutum L. Unravels Their Roles in Flowering - Ren, Zhongying; Yu, Daoqian; Yang, Zhaoen; Li, Changfeng; Qanmber, Ghulam; Li, Yi; Li, Jie; Liu, Zhao; Lu, Lili; Wang, Lingling; Zhang, Hua; Chen, Quanjia; et al. (Frontiers in Plant Science, 2017)
Cotton is one of the major world oil crops. Cottonseed oil meets the increasing demand of fried food, ruminant feed and renewable bio-fuels. MADS intervening keratin-like and C-terminal (MIKC)-type MADS-box genes encode transcription factors that have crucial roles in various plant developmental processes. Nevertheless, this gene family has not been characterized, nor its functions investigated, in cotton. Here, we performed a comprehensive analysis of MIKC-type MADS genes in the tetraploid Gossypium hirsutum L., which is the most widely cultivated cotton species. In total, 110 GhMIKC genes were identified and phylogenetically classified into 13 subfamilies. The Flowering locus C (FLC) subfamily was absent in the Gossypium hirsutum L. genome but is found in Arabidopsis and Vitis vinifera L.. Among the genes, 108 were distributed across the 13 A and 12 of the D genome’s chromosomes, while two were located in scaffolds. GhMIKCs within subfamilies displayed similar exon/intron characteristics and conserved motif compositions. According to RNA-sequencing, most MIKC genes exhibited high flowering-associated expression profiles. A quantitative real-time PCR analysis revealed that some crucial MIKC genes determined the identities of the five flower organs. Furthermore, the overexpression of GhAGL17.9 in Arabidopsis caused an early flowering phenotype. Meanwhile, the expression levels of the flowering-related genes CONSTANS (CO), LEAFY (LFY) and SUPPRESSOR OF OVEREXPRESSION OF CONSTANS1 (SOC1) were significantly increased in these lines. These results provide useful information for future studies of GhMIKCs’ regulation of cotton flowering.